Recommendations on Postoperative Activities After Abdominal Operations and Incisional Hernia Repair—A National and International Survey - Schaaf, Sebastian; Schwab, Robert; Güsgen, Christoph; Vilz, Tim O.; Willms, Arnulf (Frontiers in Surgery, 2021)
Background There is no conclusive data on postoperative recommendations after abdominal and hernia surgery and there is significant variation in the literature on that question. Thus, this study evaluates the status quo of recommendations of postoperative activity restriction after abdominal surgery. Material and Methods Data from a national (German) and international survey of general surgeons on postoperative recommendations after abdominal and hernia surgery was pooled and analyzed. Results 74.6% recommended postoperative reduced activity for 2 weeks or less after laparoscopy. For midline laparotomy 48.8% considered a reduced activity of 4 weeks or less to be sufficient. A majority from the national survey recommended more than 4 weeks instead (60.2%), whereas only 31.5% from the international survey did so (p=0.000). In the pooled analysis, 258 of 450 (57.3%) rated 4 weeks or less suitable. However, the recommendations differed significantly between the surveys (4 weeks or less: a national survey, 47.1% vs. international survey, 64.6%; p=0.000). Conclusion There was substantial variation in the given recommendations. However, we found no evidence against immediate mobilization, reduced physical activity and lifting for up to 2 weeks after laparoscopic surgery and for up to 4 weeks after open abdominal surgery and open incisional/ventral hernia repair in uncomplicated and standard cases. There might be individual and socio-economic benefits to earlier allow patients to return to their full individual level of activity and work without putting them at risk of complications.